Comprehensive study of crystalline AlN/sapphire templates after high-temperature annealing with various sputtering conditions. (December 2020) - Gu, Wen; Liu, Zhibin; Guo, Yanan; Wang, Xiaodong; Jia, Xiaolong; Liu, Xingfang; Zeng, Yiping; Wang, Junxi; Li, Jinmin; Yan, Jianchang
Abstract: High-quality AlN/sapphire templates were fabricated by the combination of sputtering and high-temperature (HT) annealing. The influence of sputtering parameters including nitrogen flux, radio frequency power, and substrate temperature on the crystalline quality and surface morphology of annealed AlN films were investigated. With lower substrate temperature, lower power, and lower N2 flux, the full width at half maximum of the X-ray rocking curve for AlN (0002) and (10 2) were improved to 97.2 and 259.2 arcsec after high-temperature annealing. This happens because the increased vacancy concentration of sputtered AlN films can facilitate the annihilation of dislocations by increasing the recovery rate during HT annealing. Step and step-bunching morphologies were clearly observed with optimized sputtering conditions.